Literasi Agama Sebagai Alternatif Pendidikan Al-Qur’an Di Desa Lembar Selatan - Al Jumhuri, Muh. Asroruddin; Samsul Hakim; Alfan Hadi; Sunardi Utami; Yuliana; Sanimah; Martini; Saptini; M. Izrar; Ridwanullah; Sadam Paksindra; Vatimatuz Zakhrah; Zahroyani; Muhammad Holkin (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
This community service aims to study religious literacy as an alternative to Qur'anic education in Lembar Selatan Village, West Lombok Regency. The method used in the implementation of this community service is the planning stage, preparation stage, implementation stage. The results of this service show that religious literacy has great potential in improving the understanding and religious practices of the people of Lembar Selatan Village. Nevertheless, there are challenges in its implementation, including the professionalism of community service work that is less effective and efficient and the lack of adequate educational facilities and infrastructure.